Adaptasi Belajar Baca Kitab Kuning Model Sidogiri di Ponpes As-Sunniyyah Al-Jauhari Jember - Muhammad Bahrul Ula (Al-Fusha : Arabic Language Education Journal, 2022)
The ability of reading yellow book is a necessary requirement for students at Ponpes As-Sunniyyah Al-Jauhari Kencong Jember. Al-Miftāḥ li al-ʻUlūm method as the Sidogiri model is adapted to improve the ability of the students of Ponpes As-Sunniyyah Al-Jauhari Kencong Jember in reading the yellow book. This article pointed to describe the implementation of the Al-Miftāḥ li al-ʻUlūm method as a Sidogiri model at Ponpes As-Sunniyyah Al-Jauhari Kencong Jember. This article uses a qualitative method to analyze the data descriptively. The results exposed that the Sidogiri model could be coherent with the learning climate at Ponpes As-Sunniyyah Al-Jauhari Kencong Jember and in accordance with the expectations of Ponpes As-Sunniyyah Al-Jauhari Kencong Jember to make reading the yellow book effective. The Al-Miftāḥ li al-ʻUlūm method as the Sidogiri model can be an alternative model for the acceleration of reading the yellow book in the pesantren environment.